Potential Estimination of Medical Plant in Jompi Forest Muna District - . Ernikawati; Ervizal A. M. Zuhud; Yanto Santosa (Media Konservasi, 2017)
Medicinal plants are all plant species that produce one or more active components used for health care and treatment or all plant species known or believed to have medicinal properties. The purpose of this research are as follows: 1) Analyzing the diversity of plant species of tree berhabitus medicinal in Hutan lindung Jompi and 2) Assessing and predicting the potential of superior medicinal plants. The research method used is vegetation analysis method, with plot size 100 x 100 m2. In addition, interviews were conducted with community leaders who understood the benefits of medicinal plants. The importance of medicinal plants is seen based on the number of people using and medicinal plants that have been identified on a national scale. The results show that the total number of 76 species diversity is the most widely used by the community of 24 species. Part of medicinal plants used are root, bark, seeds, sap and the most dominant used is the leaves. To treat diseases such as fever, cough, diabetes, antiseptic, abdominal pain and mouth ulcers. It has been identified and has a market value on a national scale. The main conclusions of this study are Jompi's protected forests have a high diversity, diversity of benefits and habitus diversity. This is based on the diversity of species that commercially potential local communities have exploited. Keywords: medicinal plants, protected forest, species diversity